The Climb from Salt Lick : a Memoir of Appalachia - Abrams, Nancy, 1953- (Project Muse, 2018)
In the mid-1970s, Nancy L. Abrams, a young photojournalist from the Midwest, plunges into life as a small-town reporter in West Virginia. She befriends the hippies on the commune one mountaintop over, rents a cabin in beautiful Salt Lick Valley, and falls in love with a local boy, wrestling to balance the demands of a job and a personal life. She learns how to survive in Appalachia--how to heat with coal and wood, how to chop kindling, plant a garden, and preserve produce. The Climb from Salt Lick is the remarkable memoir of an outsider coming into adulthood. It is the story of a unique place and its people from the perspective of a woman who documents its burdens and its beauty, using words and pictures to tell the rich stories of those around her.